THE METHOD OF OPERATOR’S ACTIVITY ESTIMATION FOR THE AUTOMATED CONTROL SYSTEM IN AERATED CONCRETE PRODUCTION - Кaminska Zh. К.; Serdiuk, S. N.; Kulynych E. М. (Radio Electronics, Computer Science, Control, 2019)
Context. The problem of quantitative estimation of the Automated Control System operator’s activity for aerated concrete production is considered. The relevance of the problem is determined by the need to take into account the human factor in the development of systems of this type. The research object is the ergonomic and psychological-engineering support in the activity of Automated Control System operator for aerated concrete production. Models, methods and means for increasing the efficiency of the operator’s activity are the research subject for a type of the manufacturing considered. Objective. The method of conducting an ergonomic examination of the Automated Control System operator’s activity based on quantitative indicators of this activity was proposed as a solution. The quantitative indicators were obtained as the results of a simulation. The method verification took place by the example of the analysis of Automated Control System operator’s activity in dosing materials for manufacturing aerated concrete at JSC “Motor Sich” (Zaporizhzhia, Ukraine). Method. The solution offered includes the imitation model of Automated Control System operating process for the aerated concrete preparation and operator’s interaction with the analyzed human-machine interface version. The estimation of the operator’s activity is based on a comparative analysis of the results of an experiment with a battery of regulating and marginal indicators introduced into the model as for characterizing the operator’s activities. The “operator-Automated Control System” human-machine system incorporated into the imitation model is presented as a queuing system. Results. The research resulted in software to realize the offered method of quantitative estimation of the Automated Control System operator’s activity for aerated concrete production. Conclusions. The research proposes the method of quantitative estimation of operator’s activity for aerated concrete production based on a stochastic combined model. Offered model is a further development of the combined model proposed by the authors earlier. Unlike the combined model, the stochastic combined model takes into account random effects in the “operator-Automated Control System” system and the operator’s activity formalization to eliminate such impacts. The conducted experiments have proved the operability of the software offered; such software can be recommended to be used while justifying the control methods, different human-machine interface prototypes variants to keep them optimized on criteria of the required efficiency and quality concerning the operator’s activity for aerated concrete production.